DIVERSITY OF WETLAND FISH AND ITS IMPACT ON THE INCOME OF FISHERMEN COMMUNITY OF ASSAM - DEKA, TAPAN KUMAR; KAKATI, M.; GOSWAMI, M. M. (Journal of Indian Fisheries Association, 2015)
A survey was conductd in 3,000 fishermen households surrounding 54wetlands (Beels) of Assam. The fish diversity of the wetlands has beendecreasing during the last few years due to some extrinsic and intrinsicfactors. The total number of fish species recorded so far during the presentstudy is 67 belonging to 21 families. Cyprinidae is the most dominant familyrepresented by major group species (8), intermediate group species (3) andminor group species (12) of high commercial value. Among these three groups,the diversity of fish species is higher in the minor group fish. The presentpaper deals with the economic condition of the fishermen who mainly fishin the wetlands. The economic condition of the fishermen community isfound very poor. The income of fishermen varies from Rs.4,4 78.00 to Rs. 7,484.00per annum. A regression analysis shows that the income of fishermen is notdependent alone on the fish production but it is exclusively dependent onthe value of the fish catch. All the three groups (in terms of value) havesignificant influence at 10.00% confidence level. But analysis of~ shows thatthe intermediate fish group exhibits the highest influence on the variationof the fishermen income followed by minor and major group respectively.Keywords :Fish diversity, Fishermen, Fishing income, Wetlands